Estimating the Relative Sociolinguistic Salience of Segmental Variables in a Dialect Boundary Zone - Llamas, Carmen; Watt, Dominic; MacFarlane, Andrew E. (Frontiers in Psychology, 2016)
One way of evaluating the salience of a linguistic feature is by assessing the extent to which listeners associate the feature with a social category such as a particular socioeconomic class, gender, or nationality. Such ‘top–down’ associations will inevitably differ somewhat from listener to listener, as a linguistic feature – the pronunciation of a vowel or consonant, for instance – can evoke multiple social category associations, depending upon the dialect in which the feature is embedded and the context in which it is heard. In a given speech community it is reasonable to expect, as a consequence of the salience of the linguistic form in question, a certain level of intersubjective agreement on social category associations. Two metrics we can use to quantify the salience of a linguistic feature are (a) the speed with which the association is made, and (b) the degree to which members of a speech community appear to share the association. Through the use of a new technique, designed as an adaptation of the Implicit Association Test, this paper examines levels of agreement among 40 informants from the Scottish/English border region with respect to the associations they make between four key phonetic variables and the social categories of ‘Scotland’ and ‘England.’ Our findings reveal that the participants exhibit differential agreement patterns across the set of phonetic variables, and that listeners’ responses vary in line with whether participants are members of the Scottish or the English listener groups. These results demonstrate the importance of community-level agreement with respect to the associations that listeners make between social categories and linguistic forms, and as a means of ranking the forms’ relative salience.